A kind of water-retaining ceramsite and preparation method thereof

The water-retaining ceramic granules prepared by using dust removal ash, cement and water-absorbing resins have solved the problem of insufficient water retention ability of traditional ceramic granules, and achieved high water absorption, water retention and breathability of ceramic granules, which are suitable for the production of garden ceramic granules.

CN116081969BActive Publication Date: 2025-03-14LIUZHOU LIUJING TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211522188.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2025-03-14
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

Traditional garden ceramics have poor water retention ability, and the moisture in the ceramics is prone to evaporation and loss, which cannot meet the market's demand for high water absorption, water retention and breathability.

Method used

Dust removal ash, cement and water-absorbing resin (a mixture of polyacrylate and polyacrylamide) are used as raw materials, and water-retaining ceramic granules with particle sizes of 3 to 8 mm are prepared through specific ratios and preparation processes. This process includes water absorption and pulverization of water-absorbing resin, and then stir evenly with dust removal ash and cement, granulation and natural curing, and improving the water absorption and water retention of the ceramic granules.

Benefits of technology

It significantly improves the water absorption and water retention of the ceramic granules, so that the ceramic granules can slowly release moisture for a long time, reduces the difficulty of the ceramic granules, and ensures the hardness and yield of the ceramic granules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of unfired ceramsite, and more specifically, to a water-retaining ceramsite and a preparation method thereof. The ceramsite is prepared from the following raw materials in parts by weight: 300-500 parts of dust removal ash, 80-150 parts of cement, and 50-60 parts of water-absorbent resin; the preparation method comprises the following steps: putting the water-absorbent resin after absorbing water, the dust removal ash and the cement into a mixer for stirring, putting the mixture into a disc granulator for granulation, spraying water after taking out of the pot for natural curing to obtain a finished ceramsite; the invention uses the water-absorbent resin to prepare the ceramsite, which can greatly improve the water absorption and water retention capacity of the ceramsite; the preparation process is simple, does not require high-temperature calcination, and is energy-saving and environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of unfired ceramsite preparation, and more specifically to water-retaining ceramsite and a preparation method thereof. Background Art

[0002] Ceramic granules are a kind of artificial light aggregate. They have a hard outer shell, a layer of glaze that is water-proof and air-retaining, and microporous ceramic granules inside. Ceramic granules are raw materials for building materials. Their main function is to reduce the bulk density of building materials and to keep them warm. There are many types of ceramsites due to different classifications. According to the production process, they are divided into two categories: sintered and unfired. In the construction field, most of them are clay sintered. With the development of the construction industry, clay resources are increasingly scarce, and clay sintered ceramsite can no longer meet the market demand.

[0003] Unfired ceramsite is mainly divided into high-strength ceramsite, ordinary ceramsite and garden ceramsite. Garden ceramsite requires bright colors, rich water absorption, high strength, rich nutrition and good air permeability. The unfired process can change any color by adding pigments, and can produce products with any nutrient content by adding nutrients. The strength, water absorption rate and air permeability can all be achieved by adjusting the formula and maintenance process. Therefore, it can process any variety of garden ceramsite to make up for the shortcomings of baked ceramsite. Traditional garden ceramsite mainly uses foaming method and other means to increase the porosity of ceramsite to achieve the purpose of high air permeability and high water absorption, but the ceramsite prepared by this method has poor water retention capacity, and the water in the ceramsite is easy to evaporate and lose quickly. Summary of the invention

[0004] In order to overcome the above problems, the present invention provides a water-retaining ceramsite and a preparation method thereof. The preparation method can effectively improve the water absorption and water retention of the ceramsite and can slowly release water over a long period of time.

[0005] On the one hand, the present invention provides a water-retaining ceramsite, which is composed of the following raw materials in parts by weight: 300-500 parts of dust removal ash, 80-150 parts of cement, and 50-60 parts of water-absorbing resin.

[0006] Furthermore, the dust removal ash is a mixture of foundry ash and recycled ash.

[0007] Furthermore, the weight ratio of the casting ash to the recycled ash is 1:1 to 2:1.

[0008] Furthermore, the water-absorbing resin is a mixture of polyacrylic acid salt and polyacrylamide.

[0009] Furthermore, the weight ratio of polyacrylic acid salt to polyacrylamide is 3:1 to 3:2.

[0010] Furthermore, the particle size of the water-retaining ceramsite is 3 to 8 mm, the compressive strength is ≥3MPa, the bulk density is 0.6kg / L≤0.9kg / L, and the water absorption rate is ≥30%.

[0011] On the other hand, the present invention also provides a method for preparing water-retaining ceramsite, which specifically comprises the following steps:

[0012] S1, mixing the water-absorbing resin, dust removal ash and cement after absorbing water to obtain a mixture;

[0013] S2, granulating the mixed material, and then spraying water for natural curing to obtain the water-retaining ceramsite.

[0014] Furthermore, the water-absorbing resin after absorbing water in step S1 is obtained by washing the water-absorbing resin with water and then crushing it.

[0015] Furthermore, the particle size of the water-absorbing resin after absorbing water in step S1 is 200-300 meshes.

[0016] Furthermore, the stirring time in step S1 is 150 to 200 seconds.

[0017] Furthermore, in step S2, granulation is performed by a granulator, the rotation speed of the granulator is 100 to 200 rpm, and the granulation time is 90 to 130 minutes.

[0018] The significant advantages of the present invention are:

[0019] (1) The present invention prepares a water-retaining ceramsite using a water-absorbing resin. The water-absorbing resin is a material with excellent water-retaining capacity. It has the ability to absorb water that is several hundred to several thousand times heavier than its own weight and can slowly release water over a long period of time. The water-retaining ceramsite, calculated by weight, includes the following raw material components: 300 to 500 parts of dust removal ash, 80 to 150 parts of cement, and 50 to 60 parts of water-absorbing resin. The use of this amount of water-absorbing resin in combination with other components to prepare ceramsite will greatly improve the water-retaining capacity of the ceramsite. At the same time, the water-absorbing resin releases water during the curing process, which reduces the difficulty of curing the ceramsite.

[0020] (2) The present invention prepares a water-retaining ceramsite by controlling the order of adding raw materials so that the water-absorbing resin is fully absorbed with water before preparing the ceramsite. This can prevent the resin from absorbing water during the curing process of the ceramsite, which causes the hydration reaction of the cement to be unable to proceed and the granulation to fail. At the same time, because the water-absorbing resin expands after absorbing water, directly mixing the water-absorbing resin that has not absorbed water with other raw materials for granulation will cause the resin to absorb water and swell, destroying the ceramsite structure. DETAILED DESCRIPTION

[0021] A water-retaining ceramsite is proposed for this specific implementation. The raw materials of the water-retaining ceramsite include dust removal ash, cement and water-absorbing resin. The water-absorbing resin is a material with excellent water-retaining capacity, which can slowly release water over a long period of time; the raw materials of the water-retaining ceramsite, calculated by weight fraction, include the following components: 300-500 parts of dust removal ash, 80-150 parts of cement, and 50-60 parts of water-absorbing resin; the dust removal ash in the proportion is a mixture of casting ash and recycled ash; the weight ratio of the casting ash and recycled ash is 1:1-2:1; the water-absorbing resin is a mixture of polyacrylic acid salt and polyacrylamide, and the polyacrylic acid salt and polyacrylamide are mixed to balance and improve the water absorption and water-retaining capacity of the ceramsite; the weight ratio of the polyacrylic acid salt and polyacrylamide is 3:1-3:2; the particle size of the water-retaining ceramsite is 3-8mm, the compressive strength is ≥3MPa, the bulk density is 0.6kg / L≤≤0.9kg / L, and the water absorption rate is ≥30%, and it has better hardness and water absorption.

[0022] This specific embodiment also proposes a method for preparing water-retaining ceramsite, which comprises the following steps:

[0023] S1, the water-absorbing resin, dust removal ash and cement are stirred evenly to obtain a mixture; the particle size of the water-absorbing resin after water absorption is 200-300 meshes, and the particle size of the water-absorbing resin is reasonably controlled to avoid the water retention performance being reduced due to the increase of specific surface area when the particle size is too small, and the water absorption is reduced due to the difficulty of water absorption in the center of the resin particles when the particle size is too large; the stirring time is 150-200s; the water-absorbing resin after water absorption is immersed in water for 580-620s, and the water-absorbing resin completely absorbed with water is broken up to obtain;

[0024] S2, granulating the mixture, and then spraying water for natural curing to obtain the water-retaining ceramsite; further, granulating the mixture by a granulator, the rotation speed of the granulator is 100-200 rpm, and the granulation time is 90-130 min.

[0025] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.

[0026] Example 1

[0027] The invention discloses a water-retaining ceramsite. Each raw material is prepared according to weight proportion, wherein the raw material comprises 200g of foundry ash, 200g of recycled ash, 115g of cement, 33g of polyacrylic acid salt and 22g of polyacrylamide.

[0028] The water-retaining ceramsite in the present embodiment is prepared by the following steps:

[0029] (1) Weigh the water-absorbent resin, immerse it in water for 600 seconds, and crush it into a particle size of 200 to 300 meshes after the water-absorbent resin is completely absorbed by water;

[0030] (2) Weigh dust ash and cement, put the water-absorbent resin, dust ash and cement fully absorbed into a mixer and stir for 180 seconds;

[0031] (3) The mixed material was placed in a disc granulator at a rotation speed of 150 rpm, and 20% of the weight of the mixed material was added and stirred for 110 minutes to perform granulation;

[0032] (4) spraying water after taking out of the pot and naturally curing for 7 days to obtain the water-retaining ceramsite.

[0033] Example 2

[0034] The invention discloses a water-retaining ceramsite. Each raw material is mixed according to weight proportion, wherein the raw material comprises 150g of foundry ash, 150g of recycled ash, 80g of cement, 30g of polyacrylic acid salt and 20g of polyacrylamide.

[0035] The specific preparation process is as follows:

[0036] (1) Weigh the water-absorbent resin, immerse it in water for 600 seconds, and crush it into a particle size of 200 to 300 meshes after the water-absorbent resin is completely absorbed by water;

[0037] (2) Weigh dust ash and cement, put the water-absorbent resin, dust ash and cement fully absorbed into a mixer and stir for 180 seconds;

[0038] (3) The mixed material was placed in a disc granulator at a rotation speed of 150 rpm, and 20% of the weight of the mixed material was added and stirred for 110 minutes to perform granulation;

[0039] (4) spraying water after taking out of the pot and naturally curing for 7 days to obtain the water-retaining ceramsite.

[0040] Example 3

[0041] A water-retaining ceramsite, wherein each raw material is mixed according to parts by weight, wherein the amount of foundry ash is 250g, the amount of recycled ash is 250g, the amount of cement is 150g, the amount of polyacrylic acid salt is 36g, and the amount of polyacrylamide is 24g.

[0042] The specific preparation process is as follows:

[0043] (1) Weigh the water-absorbent resin, immerse it in water for 600 seconds, and crush it into a particle size of 200 to 300 meshes after the water-absorbent resin is completely absorbed by water;

[0044] (2) Weigh dust ash and cement, put the water-absorbent resin, dust ash and cement fully absorbed into a mixer and stir for 180 seconds;

[0045] (3) The mixed material was placed in a disc granulator at a rotation speed of 150 rpm, and 20% of the weight of the mixed material was added and stirred for 110 minutes to perform granulation;

[0046] (4) spraying water after taking out of the pot and naturally curing for 7 days to obtain the water-retaining ceramsite.

[0047] Comparative Example 1

[0048] This comparative example prepares a comparative sample with a small amount of water-absorbing resin added for performance comparison. In this comparative example, the raw materials are prepared according to the weight proportions in Example 1, including 200g of foundry ash, 200g of recycled ash, 115g of cement, 15g of polyacrylic acid salt, and 15g of polyacrylamide.

[0049] The specific preparation process is as follows:

[0050] (1) Weigh the water-absorbent resin, immerse it in water for 600 seconds, and crush it into a particle size of 200 to 300 meshes after the water-absorbent resin is completely absorbed by water;

[0051] (2) Weigh dust ash and cement, put the water-absorbent resin, dust ash and cement fully absorbed into a mixer and stir for 180 seconds;

[0052] (3) The mixed material was placed in a disc granulator at a rotation speed of 150 rpm, and 20% of the weight of the mixed material was added and stirred for 110 minutes to perform granulation;

[0053] (4) spraying water after taking out of the pot and naturally curing for 7 days to obtain the water-retaining ceramsite.

[0054] Comparative Example 2

[0055] This comparative example prepares a comparative sample with excessive water-absorbing resin added for performance comparison. In this comparative example, each raw material is prepared according to the weight proportion in Example 1, wherein foundry ash is 200g, recycled ash is 200g, cement is 115g, polyacrylate is 45g, and polyacrylamide is 45g.

[0056] The specific preparation process is as follows:

[0057] (1) Weigh the water-absorbent resin, immerse it in water for 600 seconds, and crush it into a particle size of 200 to 300 meshes after the water-absorbent resin is completely absorbed by water;

[0058] (2) Weigh dust ash and cement, put the water-absorbent resin, dust ash and cement fully absorbed into a mixer and stir for 180 seconds;

[0059] (3) The mixed material was placed in a disc granulator at a rotation speed of 150 rpm, and 20% of the weight of the mixed material was added and stirred for 110 minutes to perform granulation;

[0060] (4) spraying water after taking out of the pot and naturally curing for 7 days to obtain the water-retaining ceramsite.

[0061] Comparative Example 3

[0062] In this comparative example, all raw materials were mixed and granulated at the same time as a comparative sample for performance comparison. In this comparative example, each raw material was prepared according to the weight proportion in Example 1, wherein foundry ash was 200 g, recycled ash was 200 g, cement was 115 g, polyacrylate was 33 g, and polyacrylamide was 22 g.

[0063] The specific preparation process is as follows:

[0064] (1) Weigh the water-absorbing resin, dust removal ash and cement respectively, put them into a mixer and stir for 180 seconds;

[0065] (2) placing the mixture into a disc granulator at a rotation speed of 150 rpm, adding 20% ​​of the weight of the mixture into water and stirring for 110 min to granulate;

[0066] (3) spraying water after taking out of the pot and naturally curing for 7 days to obtain the water-retaining ceramsite.

[0067] Comparative Example 4

[0068] In this comparative example, the dust-free ash is prepared as a comparative sample for performance comparison. In this comparative example, the raw materials are prepared according to the weight proportions in Example 1, including 120g of cement, 45g of polyacrylic acid salt, and 15g of polyacrylamide.

[0069] The specific preparation process is as follows:

[0070] (1) Weigh the water-absorbent resin, immerse it in water for 600 seconds, and crush it into a particle size of 200 to 300 meshes after the water-absorbent resin is completely absorbed by water;

[0071] (2) Weigh cement, put the water-absorbent resin and cement fully absorbed into a mixer and stir for 180 seconds;

[0072] (3) The mixed material was placed in a disc granulator at a rotation speed of 150 rpm, and 20% of the weight of the mixed material was added and stirred for 110 minutes to perform granulation;

[0073] (4) spraying water after taking out of the pot and naturally curing for 7 days to obtain the water-retaining ceramsite.

[0074] Comparative Example 5

[0075] In this comparative example, a sample lacking cement is prepared as a comparative sample for performance comparison. In this comparative example, the raw materials are prepared according to the weight proportions in Example 1, wherein the foundry ash is 200 g, the recycled ash is 200 g, the polyacrylic acid salt is 45 g, and the polyacrylamide is 15 g.

[0076] The specific preparation process is as follows:

[0077] (1) Weigh the water-absorbent resin, immerse it in water for 600 seconds, and crush it into a particle size of 200 to 300 meshes after the water-absorbent resin is completely absorbed by water;

[0078] (2) Weigh the dust removal ash, put the water-absorbing resin and dust removal ash fully absorbed into the feed machine and stir for 180 seconds;

[0079] (3) The mixed material was placed in a disc granulator at a rotation speed of 150 rpm, and 20% of the weight of the mixed material was added and stirred for 110 minutes to perform granulation;

[0080] (4) spraying water after taking out of the pot and naturally curing for 7 days to obtain the water-retaining ceramsite.

[0081] The relevant properties of the ceramsite of the embodiment and the comparative example were tested, and the test results are shown in Table 1:

[0082] Table 1 Related performance parameters of ceramsite

[0083]

[0084] Comparing the experimental data of Examples 1 to 3 with the experimental data of Comparative Examples 1 to 5, it can be seen that the water-retaining ceramsite prepared by the present invention has a significant water-retaining effect while ensuring the yield rate.

[0085] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.

Claims

1. A water-retaining ceramsite, characterized in that: Calculated by weight, the raw materials include the following components: 300-500 parts of dust ash, 80-150 parts of cement, and 50-60 parts of water-absorbing resin. The water-absorbing resin is a mixture of polyacrylic acid salt and polyacrylamide, and the weight ratio of the polyacrylic acid salt to the polyacrylamide is 3:1-3:

2. After absorbing water, the particle size of the water-absorbing resin is 200-300 meshes, the particle size of the water-retaining ceramsite is 3-8mm, the compressive strength is ≥3MPa, the bulk density is 0.6kg / L≤≤0.9kg / L, and the water absorption rate is ≥30%.

2. A water-retaining ceramsite according to claim 1, characterized in that: The dust removal ash is a mixture of foundry ash and recycled ash.

3. A water-retaining ceramsite according to claim 2, characterized in that: The weight ratio of the casting ash to the recycled ash is 1:1 to 2:

1.

4. A method for preparing the water-retaining ceramsite according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, mixing the water-absorbing resin, dust removal ash and cement after absorbing water to obtain a mixture; S2, granulating the mixed material, and then spraying water for natural curing to obtain the water-retaining ceramsite.

5. The method for preparing water-retaining ceramsite according to claim 4, characterized in that: In step S1, the particle size of the water-absorbing resin after absorbing water is 200-300 meshes.

6. The method for preparing water-retaining ceramsite according to claim 4, characterized in that: The stirring time in step S1 is 150 to 200 seconds.

7. The method for preparing water-retaining ceramsite according to claim 4, characterized in that: In step S2, granulation is performed by a granulator, the rotation speed of the granulator is 100-200 rpm, and the granulation time is 90-130 min.

Citation Information

Patent Citations

  • Spheroidal attapulgite flower ceramsite with moisture-holding function

    CN102503280A

  • Casting-fly-ash ceramsite and preparation method thereof

    CN106082841A

  • Vibration-pressing-free self-curing cement stabilized macadam mixture as well as preparation method and application thereof

    CN114031337A